CoCl2-doped polyaniline composites as electrode materials with enhanced electrochemical performance for supercapacitor application - Majhi, Malati; Choudhary, R.B.; Thakur, Anukul K.; Omar, Fatin Saiha; Duraisamy, Navaneethan; Ramesh, Kasi; Ramesh, Subramaniam (Springer Verlag (Germany), 2018)
HCl-doped polyaniline (PANI) and polymeric composites of polyaniline– cobalt chloride (PANI–CoCl2) were synthesized in the laboratory via an in situ oxidative polymerization technique. Their chemical, structural and morphological properties were examined through FESEM, XRD, EDX and FTIR spectroscopic techniques. The electrochemical performance of the as-prepared composites was examined through cyclic voltammogram, electrochemical impedance spectroscopy and galvanostatic charge/discharge measurement techniques. The thermal properties of the as-prepared composites were examined through thermal gravimetric analysis technique. The results obtained were found satisfactory and well suitable for its use as hybrid electrode materials for supercapacitor application.